Writing useful, accessible, and legally defensible psychoeducational reports - Hass, Michael R.; Carriere, Jeanne Anne M. (Wiley, 2014)
"This important new resource offers practical guidance on writing psychoeducational reports that directly respond to referral concerns. The authors provide recommendations and assessment information in a format easily understood by parents, teachers, and other educational and mental health professionals. Filled with numerous practice exercises, sample reports, helpful checklists, and end of chapter questions, this invaluable guide provides an approach to writing reports that will help school psychologists better meet the needs of the individualized education program (IEP) team, teachers, parents, and others working with the child"--Provided by publisher.